Cement concrete with high anti-cracking function and production method thereof
By using agarose aerogel and modified fiber components in cement concrete, the problem of prone to cracks in cement concrete is solved, which significantly improves its crack resistance and mechanical properties, extends the service life of the structure and enhances the resistance to external forces. .
Patent Information
- Application Number
- CN202411492660.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-07
AI Technical Summary
Existing cement concrete is prone to cracks during use, resulting in a decrease in structural durability and is difficult to meet crack resistance requirements in projects with high mechanical properties.
Using agarose aerogel and modified fiber components, the mechanical properties and crack resistance of concrete are improved through chemical modification treatment, and the porous structure of agarose aerogel absorbs and releases moisture, delays cement hydration, and is modified. The fiber components enhance the bonding force of cement particles and improve the compactness and strength of concrete.
It significantly improves the crack resistance and mechanical properties of concrete, extends the service life of the structure, enhances the resistance to external force damage, and reduces the risk of early self-shrinkage and cracking.
Smart Images

Figure CN119263735A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, and in particular to a cement concrete with high crack resistance and a production method thereof. Background Art
[0002] In recent years, with the development of economy and the progress of science and technology, the scale of construction of various social infrastructure has been continuously expanded, and building materials have increasingly shown their important position. Among them, cement concrete is one of the main structural materials for the construction of infrastructure such as buildings, roads, railways, and bridges. It is an artificial stone made of cementitious materials, coarse and fine aggregates, water, admixtures, etc. in a certain proportion, which is evenly stirred, densely formed, and cured and hardened.
[0003] With the continuous development of the construction field and the construction raw materials industry, higher requirements are also placed on the performance of concrete. During the use of ordinary cement concrete, due to hydration reaction and water evaporation, the mortar loses water seriously, resulting in more cracks. After the mortar is poured, if its surface is exposed to the air, fine cracks will form in the mortar due to water migration. The small cracks will expand rapidly and intersect with each other, and then develop into larger cracks. These cracks will combine into more obvious shrinkage cracks, and cracks will cause premature damage to the concrete and reduce the durability of the structure, reducing the service life of the building. In addition, in some projects, such as high-rise buildings, bridges, tunnels, etc., there are high requirements for the mechanical properties of concrete. Improving the mechanical properties of concrete can enhance its ability to resist external damage, thereby ensuring the safety and stability of the structure.
[0004] The invention patent with the announcement number CN113788655B discloses a frost-resistant and crack-resistant concrete and its preparation method. The invention prepares sepiolite-polylactic acid composite fiber and modified mesoporous silica by adding optimized components in a targeted manner, effectively improving the workability of concrete, evenly dispersing the components, and having a good leveling effect. At the same time, it has an excellent aeration effect, and a large number of small bubbles are evenly distributed in the structure, and the air content is greater than 4.7%, which effectively improves the anti-cracking performance of concrete. Therefore, by adding optimized components in a targeted manner, an additive with excellent mechanical properties and high crack resistance can be prepared to modify cement concrete and obtain high-performance cement concrete. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide a cement concrete with high anti-cracking functionality and a production method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for producing cement concrete with high crack resistance, the cement concrete comprising the following raw materials in parts by weight: 50-70 parts of cement, 100-120 parts of sand, 90-110 parts of crushed stone, 25-35 parts of fly ash, 20-30 parts of silica fume, 5-7 parts of agarose aerogel, 4-8 parts of modified fiber components, and 30-50 parts of water;
[0008] The production method comprises the following steps:
[0009] Step 1: Add cement, sand, crushed stone, fly ash and silica fume into a mixer, set the mixer speed to 500-700 r / min, the time to 25-35 min, discharge the material, and obtain a premix;
[0010] Step 2: adding agarose aerogel, modified fiber component and water to the premix obtained in step 1, and continuing stirring for 20 to 40 minutes to obtain mortar;
[0011] Step 3: Pour the mortar obtained in step 2 into the mold, move the mold to a vibration table and vibrate it 30 to 50 times to expel the bubbles in the mortar, then transfer the mold to a standard constant temperature and humidity curing box, demold the mold after curing for 18 to 30 hours, and then place it in a water tank at a constant temperature of 18 to 22°C for curing to obtain cement concrete.
[0012] Furthermore, the preparation method of the agarose aerogel comprises the following steps:
[0013] Step I: Add agarose and deionized water to a nitrogen-protected reactor. After the addition, turn on the heating until the temperature in the reactor reaches 80-90°C, stir and mix, then add 2-chloroacrylic acid and catalyst A, keep warm and stir for 4-6 hours, cool and discharge, and obtain modified agarose;
[0014] Step II: Add modified agarose to the dimethyl sulfoxide solution, stir mechanically to evenly, add sodium 2,3-dimercaptopropane sulfonate and a photoinitiator, react under ultraviolet light for 3 to 5 hours, collect the product, and obtain agarose aerogel after freeze-drying.
[0015] Furthermore, in step I, the catalyst A is either sodium hydroxide or potassium hydroxide.
[0016] Furthermore, in step II, the photoinitiator is any one of benzoin ethyl ether, benzoin isopropyl ether or benzoin dimethyl ether.
[0017] Furthermore, in step II, the freeze-drying treatment is: placing the product in a mold, allowing it to stand until it gels, then storing the mold at a temperature of -18 to -22°C for 5 to 7 hours, and then placing it in a freeze dryer and freeze-drying it at a temperature of -48 to -52°C for 15 to 25 hours.
[0018] Furthermore, the method for preparing the modified fiber component comprises the following steps:
[0019] Step i: ultrasonically dispersing the palm fiber in a toluene solution to form a uniform dispersion, adding chloroacyl chloride and triethylamine to the dispersion, stirring at room temperature for 3 to 7 hours, and removing the solvent by rotary evaporation to obtain an intermediate material;
[0020] Step ii: add the intermediate material to N,N-dimethylformamide solution, ultrasonically disperse for 20 to 40 minutes, add polyamide-amine and triethylamine under continuous nitrogen conditions, raise the system temperature to 70 to 80°C under stirring conditions, keep warm for 4 to 8 hours, stop heating and remove the nitrogen, cool to room temperature and then discharge the material to obtain a modified fiber component.
[0021] Furthermore, in step i, the chloroacyl chloride is any one of 3-chloropropionyl chloride, 4-chlorobutyryl chloride or chloroacetyl chloride.
[0022] Furthermore, in step i, the mass ratio of the palm fiber to the chloroacyl chloride is 1:0.05-0.2.
[0023] Furthermore, in step three, the temperature of the standard constant temperature and humidity curing box is 18-22° C., and the humidity is 94-98%.
[0024] A cement concrete with high crack resistance is produced by adopting the production method.
[0025] Beneficial effects of the present invention:
[0026] (1) The present invention adds agarose aerogel and modified fiber components during the preparation of concrete. The raw materials cooperate with each other, so that the prepared concrete has good mechanical properties and crack resistance, and can be widely used in various engineering constructions.
[0027] (2) The present invention prepares agarose aerogel as a filling modifier for concrete. Since the aerogel contains a large number of hydrophilic groups and a porous structure, it can absorb a portion of water and store it in the pores at the initial stage of curing. In the later stage of curing, due to the aging and shrinkage of the aerogel, the absorbed water is gradually released, promoting cement hydration, thereby improving the mechanical properties and durability of the concrete, and helping to increase the humidity inside the concrete and reduce the risk of early self-shrinkage and cracking. In addition, the carboxyl groups in the agarose aerogel structure can react with calcium ions in the mortar to generate insoluble calcium salts, which can delay the hydration degree of cement and improve the strength of the concrete. In addition, the agarose aerogel structure contains sulfonic acid groups, which can form complexes with calcium ions in the mortar, inhibit C3A hydration, reduce the early hydration reaction heat, and reduce the early internal temperature of the concrete, thereby helping to reduce the generation of early cracks in the concrete, and can accelerate the hydration rate of C3S and increase the amount of needle-shaped calcium aluminate in the early cement block, thereby improving the early strength of the concrete.
[0028] (3) The present invention uses a chemical connection method to graft polyamide-amine onto the surface of palm fiber to obtain a modified fiber component. Since the amide group in the modified fiber component has the characteristic of strong adsorption, the binding force between palm fiber and cement hydration products can be improved, so that cement particles are tightly adsorbed on the surface of palm fiber, thereby making the internal structure of concrete more compact and able to be evenly distributed in the mortar, thereby strengthening the continuity and homogeneity of the concrete material medium, improving the crack resistance of concrete, and effectively improving the strength of concrete. In addition, the amide group in the modified fiber component can react with calcium hydroxide in the mortar, further improving the early strength of concrete.
[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0031] Figure 1 Infrared spectrum test diagrams of agarose, modified agarose and agarose aerogel prepared in the present invention.
[0032] Figure 2 This is an infrared spectrum test chart of the modified fiber component prepared by the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The agarose aerogel and modified fiber components in the examples and comparative examples of the present invention are prepared by the following method:
[0035] 1. Preparation of agarose aerogel
[0036] Step I: Add 5 g of agarose and deionized water into a nitrogen-protected reactor. After the addition, turn on the heating until the temperature in the reactor reaches 85°C, stir and mix, then add 1 g of 2-chloroacrylic acid and 0.05 g of sodium hydroxide, keep warm and stir for 5 hours, cool and discharge, and obtain modified agarose;
[0037] Step II: Add 5 g of modified agarose to the dimethyl sulfoxide solution, stir mechanically, add 1.4 g of sodium 2,3-dimercaptopropane sulfonate and 0.08 g of benzoin ethyl ether, react for 4 hours under ultraviolet light at a wavelength of 365 nm, collect the product, and then place the product in a mold, let it stand until it gels, then place the mold at a temperature of -20°C and store it for 6 hours, then place it in a freeze dryer, and freeze-dry it at a temperature of -50°C for 20 hours to obtain agarose aerogel.
[0038] Agarose, modified agarose and agarose aerogel were analyzed by infrared spectroscopy using a FTIR-850 Fourier transform infrared spectrometer (Tianjin Gangdong Technology Development Co., Ltd.). Figure 1 As shown by Figure 1 It can be seen that in the infrared spectrum of agarose, 3290cm -1 The absorption peak of hydroxyl group appears at 1050cm -1 The absorption peak of ether bond COC appears at 3020cm -1 The absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 1730 cm -1 The absorption peak of the carboxyl group C=O appears at 1026 cm -1 The absorption peak of ether-bonded COC appears at 1004 cm -1 The absorption peak of ether bond COC appears at 1735 cm -1 The absorption peak of the carboxyl group C=O appears at 1280 cm -1 and 1036cm -1The absorption peak of sulfonic acid group appears at 1191cm -1 The absorption peak of CSC appears at , and the absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond disappears.
[0039] Technical principle: In agarose aerogel, firstly, the structure of agarose contains active hydroxyl groups, which can undergo substitution reaction with the halogen functional groups in the structure of 2-chloroacrylic acid under the action of sodium hydroxide, thereby introducing unsaturated olefinic functional groups and carboxyl groups into the structure of agarose to obtain modified agarose; secondly, the unsaturated olefinic functional groups in the modified agarose structure are used as active sites, which can undergo click reaction with the thiol groups in the structure of sodium 2,3-dimercaptopropane sulfonate under the irradiation of benzoin ethyl ether and ultraviolet light, thereby introducing sodium 2,3-dimercaptopropane sulfonate into the structure of agarose through chemical bond connection to obtain agarose aerogel.
[0040] 2. Preparation of modified fiber components
[0041] Step i: ultrasonically disperse 6 g of palm fiber in a toluene solution to form a uniform dispersion, add 0.8 g of 4-chlorobutyryl chloride and 0.04 g of triethylamine to the dispersion, stir at room temperature for 5 h, and remove the solvent by rotary evaporation to obtain an intermediate material;
[0042] Step ii: Add 6 g of the intermediate material to the N,N-dimethylformamide solution, ultrasonically disperse for 30 minutes, add 5.2 g of polyamide-amine and 0.1 g of triethylamine under continuous nitrogen conditions, raise the system temperature to 75°C under stirring conditions, keep warm for 6 hours, stop heating and remove the nitrogen, cool to room temperature and then discharge the material to obtain a modified fiber component.
[0043] The modified fiber components were analyzed by infrared spectroscopy using a FT IR-850 Fourier transform infrared spectrometer (Tianjin Gangdong Technology Development Co., Ltd.). Figure 2 As shown by Figure 2 It can be seen that in the infrared spectrum of the modified fiber component, 1759cm -1 The absorption peak of the ester group C=O appears at 1650cm -1 The absorption peak of C=O in amide appears at 3331 cm -1 The absorption peak of NH appears at 1401cm -1 The absorption peak of CN appears at
[0044] Technical principle: In the modified fiber component, first, under the action of triethylamine, the hydroxyl groups on the surface of the palm fiber can react with the acyl chloride groups in the 4-chlorobutyryl chloride structure, and the halogen substituents are modified on the surface of the palm fiber to obtain an intermediate material; secondly, the halogen groups in the intermediate material structure can further react with the amino groups in the polyamide-amine structure to obtain a modified fiber component.
[0045] Example 1
[0046] Preparation of cement concrete
[0047] Step 1: Add 50 parts of 42.5 grade ordinary Portland cement, 100 parts of quartz sand, 90 parts of crushed stone, 25 parts of fly ash and 20 parts of silica fume into a mixer, set the mixer speed to 500r / min, the time to 25min, discharge the material, and obtain a premix;
[0048] Step 2: Add 5 parts of agarose aerogel, 4 parts of modified fiber components and 30 parts of water to the premix obtained in step 1, and continue stirring for 20 minutes to obtain mortar;
[0049] Step 3: Pour the mortar obtained in step 2 into the mold, move the mold to a vibration table and vibrate it 30 times to expel the bubbles in the mortar, and then transfer the mold to a standard constant temperature and humidity curing box, set the temperature of the standard constant temperature and humidity curing box to 18°C and the humidity to 94%, demold after curing for 18 hours, and then put it into a constant temperature 18°C water tank for curing to obtain cement concrete.
[0050] Example 2
[0051] Preparation of cement concrete
[0052] Step 1: Add 60 parts of 42.5 grade ordinary Portland cement, 110 parts of quartz sand, 100 parts of crushed stone, 30 parts of fly ash and 25 parts of silica fume into a mixer, set the mixer speed to 600r / min, the time to 30min, discharge the material, and obtain a premix;
[0053] Step 2: Add 6 parts of agarose aerogel, 6 parts of modified fiber components and 40 parts of water to the premix obtained in step 1, and continue stirring for 30 minutes to obtain mortar;
[0054] Step 3: Pour the mortar obtained in step 2 into the mold, move the mold to the vibration table and vibrate it 40 times to expel the bubbles in the mortar, and then transfer the mold to a standard constant temperature and humidity curing box, set the temperature of the standard constant temperature and humidity curing box to 20°C and the humidity to 96%, demold after curing for 24 hours, and then put it into a constant temperature 20°C water tank for curing to obtain cement concrete.
[0055] Example 3
[0056] Preparation of cement concrete
[0057] Step 1: Add 70 parts of 42.5 grade ordinary Portland cement, 120 parts of quartz sand, 110 parts of crushed stone, 35 parts of fly ash and 30 parts of silica fume into a mixer, set the mixer speed to 700r / min, the time to 35min, discharge the material, and obtain a premix;
[0058] Step 2: Add 7 parts of agarose aerogel, 8 parts of modified fiber components and 50 parts of water to the premix obtained in step 1, and continue stirring for 40 minutes to obtain mortar;
[0059] Step 3: Pour the mortar obtained in step 2 into the mold, move the mold to a vibration table and vibrate it 50 times to expel the bubbles in the mortar, and then transfer the mold to a standard constant temperature and humidity curing box. Set the temperature of the standard constant temperature and humidity curing box to 22°C and the humidity to 98%. After curing for 30 hours, demold the mold and then put it into a water tank with a constant temperature of 22°C for curing to obtain cement concrete.
[0060] Comparative Example 1
[0061] Preparation of cement concrete
[0062] Step 1: Add 60 parts of 42.5 grade ordinary Portland cement, 110 parts of quartz sand, 100 parts of crushed stone, 30 parts of fly ash and 25 parts of silica fume into a mixer, set the mixer speed to 600r / min, the time to 30min, discharge the material, and obtain a premix;
[0063] Step 2: Add 6 parts of agarose aerogel and 40 parts of water to the premix obtained in step 1, and continue stirring for 30 minutes to obtain a mortar;
[0064] Step 3: Pour the mortar obtained in step 2 into the mold, move the mold to the vibration table and vibrate it 40 times to expel the bubbles in the mortar, and then transfer the mold to a standard constant temperature and humidity curing box, set the temperature of the standard constant temperature and humidity curing box to 20°C and the humidity to 96%, demold after curing for 24 hours, and then put it into a constant temperature 20°C water tank for curing to obtain cement concrete.
[0065] Comparative Example 2
[0066] Preparation of cement concrete
[0067] Step 1: Add 60 parts of 42.5 grade ordinary Portland cement, 110 parts of quartz sand, 100 parts of crushed stone, 30 parts of fly ash and 25 parts of silica fume into a mixer, set the mixer speed to 600r / min, the time to 30min, discharge the material, and obtain a premix;
[0068] Step 2: Add 6 parts of modified fiber component and 40 parts of water to the premix obtained in step 1, and continue stirring for 30 minutes to obtain mortar;
[0069] Step 3: Pour the mortar obtained in step 2 into the mold, move the mold to the vibration table and vibrate it 40 times to expel the bubbles in the mortar, and then transfer the mold to a standard constant temperature and humidity curing box, set the temperature of the standard constant temperature and humidity curing box to 20°C and the humidity to 96%, demold after curing for 24 hours, and then put it into a constant temperature 20°C water tank for curing to obtain cement concrete.
[0070] Comparative Example 3
[0071] Preparation of cement concrete
[0072] Step 1: Add 60 parts of 42.5 grade ordinary Portland cement, 110 parts of quartz sand, 100 parts of crushed stone, 30 parts of fly ash and 25 parts of silica fume into a mixer, set the mixer speed to 600r / min, the time to 30min, discharge the material, and obtain a premix;
[0073] Step 2: Add 6 parts of agarose aerogel, 6 parts of palm fiber and 40 parts of water to the premix obtained in step 1, and continue stirring for 30 minutes to obtain mortar;
[0074] Step 3: Pour the mortar obtained in step 2 into the mold, move the mold to the vibration table and vibrate it 40 times to expel the bubbles in the mortar, and then transfer the mold to a standard constant temperature and humidity curing box, set the temperature of the standard constant temperature and humidity curing box to 20°C and the humidity to 96%, demold after curing for 24 hours, and then put it into a constant temperature 20°C water tank for curing to obtain cement concrete.
[0075] Comparative Example 4
[0076] Preparation of cement concrete
[0077] Step 1: Add 60 parts of 42.5 grade ordinary Portland cement, 110 parts of quartz sand, 100 parts of crushed stone, 30 parts of fly ash and 25 parts of silica fume into a mixer, set the mixer speed to 600r / min, the time to 30min, discharge the material, and obtain a premix;
[0078] Step 2: Add 40 parts of water to the premix obtained in step 1 and continue stirring for 30 minutes to obtain mortar;
[0079] Step 3: Pour the mortar obtained in step 2 into the mold, move the mold to the vibration table and vibrate it 40 times to expel the bubbles in the mortar, and then transfer the mold to a standard constant temperature and humidity curing box, set the temperature of the standard constant temperature and humidity curing box to 20°C and the humidity to 96%, demold after curing for 24 hours, and then put it into a constant temperature 20°C water tank for curing to obtain cement concrete.
[0080] Performance testing:
[0081] ① The cement concrete prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4 was cured for 3 d, 7 d, and 28 d, respectively, and the flexural strength and compressive strength of the concrete were tested according to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete". The specific test results are shown in the following table:
[0082]
[0083] From the test results in the above table, it can be seen that the cement concrete prepared in Examples 1 to 3 has high flexural strength and compressive strength, and all have excellent mechanical properties; the cement concrete prepared in Comparative Example 1 does not add the modified fiber component, and the cement concrete prepared in Comparative Example 2 does not add agarose aerogel. Compared with the examples, the flexural strength and compressive strength of the cement concrete are both reduced, and the mechanical properties of the cement concrete are average, indicating that the two additives can synergistically improve the mechanical properties of the cement concrete; agarose aerogel and palm fiber are added to the cement concrete prepared in Comparative Example 3, and the flexural strength and compressive strength of the cement concrete are significantly reduced. It is speculated that this may be because the addition of unmodified palm fiber has a poor filling effect in the concrete, and the internal structure of the concrete is loose, making it difficult to effectively enhance the flexural strength and compressive strength of the concrete; the cement concrete prepared in Comparative Example 4 does not add agarose aerogel and modified fiber components, so the mechanical properties of the concrete are the worst.
[0084] ① According to JC / T 951-2005 "Test Method for Cement Mortar Crack Resistance", the cracking index test was performed on the cement concrete prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4; according to JGJ / T 70-2009 "Standard for Basic Performance Test Method of Building Mortar", the water retention performance test was performed on the cement concrete prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 4. The specific test results are shown in the following table:
[0085] Cracking index(mm) Water retention rate (%) Example 1 176 99.3 Example 2 172 99.5 Example 3 179 99.0 Comparative Example 1 195 97.9 Comparative Example 2 192 91.8 Comparative Example 3 185 96.2 Comparative Example 4 255 32.9
[0086] From the test results in the above table, it can be seen that the cement concretes prepared in Examples 1 to 3 all have excellent water retention and high crack resistance; in the cement concrete prepared in Comparative Example 1, no modified fiber component was added. Compared with the example, the cracking index of the concrete decreased significantly, and the anti-cracking performance of the concrete was poor; in the cement concrete prepared in Comparative Example 2, no agarose aerogel was added. Compared with the example, the water retention rate of the concrete decreased significantly, and the water retention performance of the concrete was average; in the cement concrete prepared in Comparative Example 3, agarose aerogel and palm fiber were added. Compared with the example, the water retention and anti-cracking performance of the concrete were average. It is speculated that this may be because the unmodified palm fiber was used for direct filling, the bonding force between the various components of the concrete and the palm fiber decreased, and the functionality of the palm fiber could not be effectively exerted, resulting in a decrease in the performance of the concrete; in the cement concrete prepared in Comparative Example 4, no agarose aerogel and modified fiber component were added, so all indicators performed poorly.
[0087] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for producing cement concrete with high crack resistance, characterized in that: The cement concrete comprises the following raw materials in parts by weight: 50 to 70 parts of cement, 100 to 120 parts of sand, 90 to 110 parts of crushed stone, 25 to 35 parts of fly ash, 20 to 30 parts of silica fume, 5 to 7 parts of agarose aerogel, 4 to 8 parts of modified fiber components, and 30 to 50 parts of water; The production method comprises the following steps: Step 1: Add cement, sand, crushed stone, fly ash and silica fume into a mixer, set the mixer speed to 500-700 r / min, the time to 25-35 min, discharge the material, and obtain a premix; Step 2: adding agarose aerogel, modified fiber component and water to the premix obtained in step 1, and continuing stirring for 20 to 40 minutes to obtain mortar; Step 3: Pour the mortar obtained in step 2 into the mold, move the mold to a vibration table and vibrate it 30 to 50 times to expel the bubbles in the mortar, then transfer the mold to a standard constant temperature and humidity curing box, demold the mold after curing for 18 to 30 hours, and then place it in a water tank at a constant temperature of 18 to 22°C for curing to obtain cement concrete.
2. The method for producing cement concrete with high crack resistance according to claim 1, characterized in that: The preparation method of the agarose aerogel comprises the following steps: Step I: under the action of catalyst A, agarose, 2-chloroacrylic acid and deionized water are added to a nitrogen-protected reactor, the temperature is increased to 80-90° C. in the reactor, and the mixture is stirred for 4-6 hours to obtain modified agarose; Step II: Under the action of a photoinitiator, add modified agarose and sodium 2,3-dimercaptopropane sulfonate to a dimethyl sulfoxide solution, mix well, irradiate with an ultraviolet lamp for 3 to 5 hours, collect the product, and obtain agarose aerogel after freeze-drying.
3. The method for producing cement concrete with high crack resistance according to claim 2, characterized in that: In step I, the catalyst A is either sodium hydroxide or potassium hydroxide.
4. The method for producing cement concrete with high crack resistance according to claim 2, characterized in that: In step II, the photoinitiator is any one of benzoin ethyl ether, benzoin isopropyl ether or benzoin dimethyl ether.
5. The method for producing cement concrete with high crack resistance according to claim 2, characterized in that: In step II, the freeze-drying treatment is as follows: placing the product in a mold, allowing it to stand until it gels, then storing the mold at a temperature of -18 to -22°C for 5 to 7 hours, and then placing it in a freeze dryer and freeze-drying it at a temperature of -48 to -52°C for 15 to 25 hours.
6. The method for producing cement concrete with high crack resistance according to claim 1, characterized in that: The method for preparing the modified fiber component comprises the following steps: Step i: under the action of triethylamine, the palm fiber and chloroacyl chloride are ultrasonically dispersed in a toluene solution, stirred at room temperature for 3 to 7 hours, and the solvent is removed to obtain an intermediate material; Step ii: Under continuous nitrogen conditions, the intermediate material, polyamide-amine and N,N-dimethylformamide solution are mixed, and stirred for 4 to 8 hours in the presence of triethylamine and a temperature of 70 to 80°C. The material is discharged after cooling to room temperature to obtain a modified fiber component.
7. The method for producing cement concrete with high crack resistance according to claim 6, characterized in that: In step i, the chloroacyl chloride is any one of 3-chloropropionyl chloride, 4-chlorobutyryl chloride or chloroacetyl chloride.
8. The method for producing cement concrete with high crack resistance according to claim 6, characterized in that: In step i, the mass ratio of the palm fiber to the chloroacyl chloride is 1:0.05-0.
2.
9. The method for producing cement concrete with high crack resistance according to claim 1, characterized in that: In step 3, the temperature of the standard constant temperature and humidity curing box is 18-22° C., and the humidity is 94-98%.
10. A cement concrete with high crack resistance, characterized in that: The method is produced according to claim 1.
Citation Information
Patent Citations
A freeze-thaw resistant and crack-resistant concrete and its preparation method
CN113788655B